Screening of catalysts and reaction conditions for the direct conversion of corncob xylan to xylitol - Ribeiro Lucília S.; Órfão José J.M.; Pereira Manuel F.R. (Green Processing and Synthesis, 2017)
Different supported metal catalysts were tested for the one-pot transformation of corncob xylan to xylitol. The influence of several factors, such as catalytic support, nature of metal, metal loading, amount of catalyst, hydrogen pressure and reaction temperature, was investigated. The results revealed that xylan can be converted into xylitol with a yield close to 80% after 2 h of reaction using Ru supported on carbon nanotubes (CNT, 0.4 wt% metal loading) with excellent stability after repeated use, at a temperature of 170°C and an H2 pressure of 50 bar. The yield of xylitol achieved is one of the highest ever reported for the direct conversion of xylan to xylitol using an environmentally friendly process.